Innovation, learning and industrial organisation - Nooteboom, Bart (1999)
Innovation, learning and organisation are analysed from a perspective which seeks to integrate evolutionary economics, the resource/competence view of the firm, an extended theory of transaction costs and insights derived from cognitive science. Firms are subject to selection by competitive forces, but they also adapt by organisational learning. Uncertainty is crucial in this, and to deal with it we need a `logic of abduction': a heuristic to move from present competence to novel competence, while surviving in the process. Such a heuristic is specified and some features are clarified by means of the notion of a script, taken from cognitive science. The heuristic is applied in an analysis of changes of industrial structure, the complementarity of large and small firms, the roles of multinational enterprises and industrial districts. - Reproduced
Keywords: Industrial organization; Industrial management